TECHNOLOGICAL PROSPECTING OF NFTS FOR INTELLECTUAL PROPERTY: A PATENT-BASED ANALYSIS - de Oliveira, Allan Jonathan Menezes; de Oliveira, Raimundo Corrêa; da Silva, Vanessa Coelho; Barboza, Ricardo da Silva (Seven Editora, 2025)
The increasing digitization of creative assets poses significant challenges to the protection of intellectual property. In this context, blockchain and Non-Fungible Token (NFT) technologies emerge as promising solutions to ensure the authenticity, traceability, and monetization of digital assets. This study aims to explore the landscape of technological innovation at this intersection through a systematic search in patent databases. The methodology consisted of a search on the Orbit Intelligence database, followed by a rigorous dual validation process that combined manual screening and analysis by Artificial Intelligence (DeepSeek), resulting in a final portfolio of 119 patent families. The results reveal a sharp increase in the number of filings from 2018 onwards, with a peak in 2022, and a strong geographical concentration in China. The analysis of technological domains indicates that innovations are focused on "IT methods for management" and "Digital communication," highlighting the use of the technology as a governance infrastructure. The qualitative analysis of selected patents demonstrates the sophistication of the solutions, which address issues ranging from registration efficiency to rights management for AI-generated content. It is concluded that the field is rapidly maturing, moving beyond proof-of-concept to develop specialized solutions that address complex challenges in the intellectual property ecosystem, thereby redefining protection paradigms in the digital economy.DOI: https://doi.org/10.56238/sevened2025.036-086